2010
DOI: 10.1590/s1519-38292010000500008
|View full text |Cite
|
Sign up to set email alerts
|

Principais causas de internação por condições sensíveis à atenção primária no Brasil: uma análise por faixa etária e região

Abstract: OBJETIVOS: analisar as tendências das principais causas de internações hospitalares entre aquelas sensíveis à atenção primária (ICSAP) no Brasil, por faixa etária e região, no período de 1999 a 2006. MÉTODOS: trata-se de um estudo ecológico misto das tendências das três principais causas de ICSAP em menores de vinte anos. Os dados secundários foram provenientes do Sistema de Informação Hospitalar (SIH-SUS) e do censo demográfico do ano de 2001 e projeções populacionais do Instituto Brasileiro de Geografia e Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
52

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 19 publications
2
29
0
52
Order By: Relevance
“…A study which aimed to assess the reliability of SIH-SUS data by comparing data with information on the patient forms suggested that 20% of ACSC admissions were not recorded (3) . However, a number of studies have highlighted the importance of investigations based on data from the SIH-SUS and consider the system an important source of data for assessing PHC (2,6,10) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study which aimed to assess the reliability of SIH-SUS data by comparing data with information on the patient forms suggested that 20% of ACSC admissions were not recorded (3) . However, a number of studies have highlighted the importance of investigations based on data from the SIH-SUS and consider the system an important source of data for assessing PHC (2,6,10) .…”
Section: Discussionmentioning
confidence: 99%
“…One potential indicator is hospital admissions for ambulatory care sensitive conditions (ACSC admissions) (5)(6) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to better understand admissions for PCSCs, Brazilian and international studies have frequently focused on their characterization and the identification of associated socio-demographic and healthcare-related variables 3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18 . Brazil has also seen analytical ecological studies that have associated the decline in admissions for PCSCs with the expansion of primary care by the Family Health Strategy (FHS) 19,20 , as well as descriptive studies on the correlation between the decline in the rates or proportions of admissions for PCSCs and the strategy's expansion in more limited geographic areas 21,22,23 .…”
Section: Introductionmentioning
confidence: 99%